(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Gender and Development orientedness in school policies is crucial for ensuring equity and inclusivity by addressing gender-based disparities and promoting equal opportunities for all students. Exploring whether a school’s policies are GAD-oriented is necessary since there are still instances of gender-based discrimination. This study aimed to determine the level of GAD orientedness school policies based on the perceptions of students. This quantitative study uses descriptive design, surveying 206 Senior High School students enrolled at Union Christian College. Weighted mean and standard deviation was used to describe the level of GAD orientedness of school policies. T-test and ANOVA were used to compare the level of GAD orientedness school policies among respondents grouped according to their profile. The respondents perceived that the level of GAD-orientedness of the school policies is high, highlighting that the student organizations and school healthcare services are the most GAD-oriented areas. Nevertheless, there is still a need to improve the sensitivity of school policies since the ratings are not fully optimal. The difference in the perceived level of sensitivity is not significant when grouped according to sex, while there is a difference in the area policy implementation and integration when grouped according to sexual orientation. The findings highlight the importance of enhancing GAD-oriented school policies for a more inclusive school environment. The proposed intervention program is recommended for adoption and enhancements of the school policies, programs, memorandum, organizations, health and well-being and school environment.